Analisis Keterampilan Membaca Permulaan Siswa Sekolah Dasar: (Studi Kasus Pada Siswa Kelas 1 SDIT Az-Zahra Cibitung) - Ade Sabrina; Herlina Usman; Siti Fatimah Azzahra (PGSD UNU NTB, 2022)
The purpose of this study is to know the factors that lead to low competence in reading students and low reading activities in schools and at home. This type of research is qualitative with this type of case study. The subject of this study is a 1st grader sdit az zahra who is having difficulty reading. The data-collection techniques used in the research include observation, interviews, and documentation. The data validation used on this research was source triangulation. The result of this study is low on reading competence because of psychological factors and family environment. The psychological factor of the student himself is not interested in reading and socio and emotional maturity and adaptation. Student activity in school life is not confident to speak up and appear before the class but when socializing with his or her classmates tends to be very active. While in his daily home activity the student who was always on his cell phone at home and rarely asked for studying and revisiting at home.Keyword: Reading, Skills, Factors